Alleyway in which Artist Thuyên's home workshop is located - Son Nguyen (22474540) (2025)
Artist Thuyên and the research team in the alleyway outside his home workshop conversing. A hand-painted sign advertising a home-based nail salon that Artist Thuyên made for his neighbour is mounted on the building on the left.